Analisis Perkembangan Dan Peluang Investasi Saham Syariah Sesuai Prinsip Islam - Muhammad David Rio Irawan (CV. ITTC INDONESIA, 2025)
Sharia-compliant stocks are shares that operate in accordance with Islamic principles, avoiding riba (usury), gharar (uncertainty), and maysir (gambling). Sharia stock investment in Indonesia continues to show significant growth, as evidenced by a 28.41% increase in the market capitalization of the Indonesia Sharia Stock Index (ISSI) in 2023, along with the rise in the number of sharia-compliant issuers to 637 stocks. This growth is driven by supportive regulations, advancements in financial technology (fintech), and the increasing public awareness of investing in accordance with sharia principles. The sharia stock market offers substantial opportunities in the halal sector, sukuk, sharia mutual funds, and Exchange Traded Funds (ETFs), providing investment stability and diversification aligned with Islamic values. However, several challenges remain, such as the low level of sharia financial literacy (39.11%), negative perceptions regarding profitability, and the limited number of sharia-compliant issuers. To address these challenges, strategic measures are needed, including public education through social media, digital campaigns, training programs, and the development of innovative sharia products. This study concludes that sharia stock investment in Indonesia holds great potential to support financial inclusion, promote halal economic growth, and contribute to sustainable development.